2015 International Conference on Informatics, Electronics &Amp; Vision (ICIEV) 2015
DOI: 10.1109/iciev.2015.7333982
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of multi-nozzle extrusion system for 3D printer

Abstract: Introduction. The main purpose of the project is the design, development and application of an extruder with five nozzles for fused filament fabrication (FFF) type 3D printers. The extruder should be able to use five different colors or materials, thus expanding the capability limits of currently existing 3D printers. Materials and methods.The fundamental design will be based on currently existing direct and Bowden extruders [1][2][3]. Firstly, the optimizations will be made on theunique extrusion mechanism wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 1 publication
0
12
0
1
Order By: Relevance
“…Therefore, this case should be considered in future research. Ali et al (2016) and Abilgaziyev et al (2015) the importance of the multi-material system for the FDM printers. A prototype of the multi-material 3D printer was presented with a detailed breakdown on design and hardware algorithms and compared with the existent multi-material FDM platforms, and it revealed that the developed platform was more simple and cheaper than the available printers in the market.…”
Section: Discussion: Materials Prediction and Optimizationmentioning
confidence: 99%
“…Therefore, this case should be considered in future research. Ali et al (2016) and Abilgaziyev et al (2015) the importance of the multi-material system for the FDM printers. A prototype of the multi-material 3D printer was presented with a detailed breakdown on design and hardware algorithms and compared with the existent multi-material FDM platforms, and it revealed that the developed platform was more simple and cheaper than the available printers in the market.…”
Section: Discussion: Materials Prediction and Optimizationmentioning
confidence: 99%
“…There are also technical solutions with a larger number of nozzles and independent kinematic systems. The research works aimed at improving existing machine designs are found as well [1,10].…”
Section: Introductionmentioning
confidence: 99%
“…Fused Deposition Modelling (FDM) is an additive processing machine that makes three-dimensional (3D) objects. Fused Filament Fabrication (FFF) machines [1] can do multicolor prints with multiple nozzles. Depending upon inside filling patterns [2]of the system that makes object strong and also useful for rapid prototype [3].…”
Section: Introductionmentioning
confidence: 99%